Investigation of bacillus zanthoxyli UMK-PNF6 inoculation effect on paddy’s growth, plant salinity stress tolerance, and its antimicrobial activities - Nur Amira Azmi (2024)
Bacillus zanthoxyli UMK-PNF6 a Plant Growth-Promoting Rhizobacteria (PGPR), is found in the rhizosphere, the area of soil that is directly impacted by plant roots. Bacillus zanthoxyli UMK-PNF6 is vital for boosting plant health and growth through a wide variety of methods. The key contributions of PGPR include nitrogen fixation, phosphate solubilization, enhanced stress tolerance, and biocontrol activity. Currently, salinity stress is a significant contributor, impacting roughly half of all irrigated land and 20% of all cultivated land, resulting in agricultural land degradation issues. Therefore, the current study is to investigate the potential of bacterial inoculation with Bacillus zanthoxyli UMK-PNF6 to promote paddy growth, improve plant tolerance to salinity stress, and display antimicrobial activity. In this experiment, paddy plants are treated with Bacillus zanthoxyli UMK-PNF6, and several growth parameters were observed such as chlorophyll content, leaf length grown (cm), and moisture content (%). The findings show that paddy growth parameters significantly improved after bacterial inoculation. Additionally, compared to untreated plants in saline circumstances, the paddy inoculated with Bacillus zanthoxyli UMK-PNF6 exhibits increased tolerance to salinity stress, as demonstrated by a higher chlorophyll content.